Pengaruh Perencanaan Pengadaan Penerimaan dan Penyimpanan Obat terhadap Kualitas Pelayanan di Instalasi Farmasi Rumah Sakit Umum Daerah Provinsi Papua Barat - Ittang Somba; Kosasih Kosasih; Ayu Laili Rahmiyati; Vip Paramarta; Taufan Nugroho (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to examine the impact of planning, procurement, receipt, and storage of medicines on pharmaceutical service quality at the Pharmacy Installation of the Regional General Hospital of West Papua Province. The research uses a quantitative approach with an explanatory design, analyzing primary and secondary data obtained through interviews and questionnaires from 100 respondents. Descriptive analysis results show that the quality of pharmaceutical management in this hospital is categorized as